Alternative Splicing Regulation During Light-Induced Germination of Arabidopsis thaliana Seeds - Tognacca, Rocío Soledad; Servi, Lucas; Hernando, Carlos Esteban; Saura-Sanchez, Maite; Yanovsky, Marcelo Javier; Petrillo, Ezequiel; Botto, Javier Francisco (Frontiers in Plant Science, 2019)
Seed dormancy and germination are relevant processes for a successful seedling establishment in the field. Light is one of the most important environmental factors involved in the relief of dormancy to promote seed germination. In Arabidopsis thaliana seeds, phytochrome photoreceptors tightly regulate gene expression at different levels. The contribution of alternative splicing (AS) regulation in the photocontrol of seed germination is still unknown. The aim of this work is to study gene expression modulated by light during germination of A. thaliana seeds, with focus on AS changes. Hence, we evaluated transcriptome-wide changes in stratified seeds irradiated with a pulse of red (Rp) or far-red (FRp) by RNA sequencing (RNA-seq). Our results show that the Rp changes the expression of ~ 20 % of the transcriptome and modifies the AS pattern of 226 genes associated with mRNA processing, RNA splicing and mRNA metabolic processes. We further confirmed these effects for some of the affected AS events. Interestingly, our RT-PCR analyses show that the Rp modulates the AS of splicing-related factors (At-SR30, At-RS31a, At-RS31 and At-U2AF65A), a light-signaling component (At-PIF6) and a dormancy-related gene (At-DRM1). Furthermore, while the phytochrome B (phyB) is responsible for the AS pattern changes of At-U2AF65A and At-PIF6, the regulation of the other alternative splicing events is independent of this photoreceptor. We conclude that (i) Rp triggers AS changes in some splicing factors, light signaling components and dormancy/germination regulators, (ii) phyB modulates only some of these AS events, and (iii) AS events are regulated by R and FR light but this regulation is not directly associated with the intensity of germination response. This data will help boosting research in the splicing field and our understanding about the role of this mechanism during the photocontrol of seed germination.